DESIGN AND ANALYSIS OF HELICAL GEAR TO OVERCOME STUCKING AND SCUFFING USING FEM - Amol Patil; A. R. Patil; Dr. S. B. Zope (International Journal of Innovations in Engineering Research and Technology, 2021)
Scuffing is one of the most common surface failure modes observed at lubricated, loaded contacts experiencing excessive relative sliding. The machine containing old gear having stucking and scuffing problem was checked for vibration analysis. Machine is among heavy duty application, these machines are operated at very high speed. In this work, analysis of high speed helical gear used in machine has been carried out. The new gear and pinion pair is designed with Gleason software of gear design consisting highest technology in gear design. Finally the result obtained by FEM analysis of old gear and new Manufacturing gear and pinion pair is again checked using a FEM and the result are compared to check the correctness. A conclusion has been arrived on the new design manufacturing gear is best suited for the machine based on the result. Basically the project involves the design and analysis of helical gear in industrial application. It is proposed to focus on reduction of vibration and better performance.